PROTECTIVE ROLE OF SAFFLOWER (Carthamus tinctorius L.) FLOWER EXTRACT-BASED NATURAL ANTIFREEZE SPRAY AGAINST FREEZING INJURY IN COMMON BEAN (Phaseolus vulgaris L.) TISSUES (Applied Biological Research, 2026)
Late spring frost is major abiotic stress factor causing significant yield losses in vegetable and fruit crops. Low temperatures induce intracellular ice formation, leading to the membrane damage, increased electrolyte leakage, and reduced tissue viability. Therefore, developing ecofriendly strategies to mitigate frost injury are essential. In this study, a natural antifreeze spray was developed using glycerol and sorbitol as osmoprotectants, safflower (Carthamus tinctorius L.) flower-extract as a natural antioxidant source, and sodium alginate as a film-forming biopolymer. The protective effect of the formulation was evaluated in buds, flowers, and young fruit tissues of common bean (Phaseolus vulgaris L.) under three temperature conditions (22-24°C, -4°C, and -10°C). Results revealed that the antifreeze treatment significantly improved tissue viability and reduced freezing-induced damage. At -10°C, cellular damage in seed tissues decreased from 82.8% to 30.0%, representing approximately 52% reduction in cell damage. Electrolyte leakage was also reduced from 97.3% to 75.0%, indicating enhanced membrane stability. Overall, the developed formulation effectively mitigated freezing damage and unveiled potential to protect cold-sensitive crops.
Keywords: Electrolyte leakage, freezing stress, natural antifreeze spray, osmoprotectants, safflower extract, TTC assay